(untitled) (Communications in Computational Chemistry, 2025)
The adsorption of organic molecules onto steel surfaces has been a key strategy in the selection of materials for mitigation of corrosion in various aggressive media. Computational chemistry offers valuable insight into the electronic interactions that govern this process. In this study, five pteridine-based compounds, namely, isoxanthopterin, leucopterin, lumazine, pterin and xanthopterin, were assessed for their adsorption behaviour and corrosion inhibition potential on Fe(110) surface using density functional theory (DFT) and molecular dynamics (MD) simulations. Geometry optimization, frontier molecular orbital analysis, and quantum reactivity descriptors were computed using the B3LYP/DNP level of theory via the Dmol³ module in BIOVIA Material Studio. Fukui indices and Mulliken charge distributions were analyzed to predict adsorption sites. Additionally, adsorption energies and molecular configurations on the Fe(110) surface were examined using the Forcite and Adsorption Locator tools. Results showed that all the studied compounds exhibit planar geometries favorable for surface interaction, with isoxanthopterin and xanthopterin demonstrating the strongest adsorption energies. Key adsorption sites were localized around nitrogen and oxygen heteroatoms. The compounds are predicted to form stable interactions with the iron surface through both physisorption and chemisorption, indicating excellent potential for use as green corrosion inhibitors.